Effect of flow diversion with silk on aneurysm size: A single center experience. Issue 1 (February 2015) - Slater, Lee-Anne; Soufan, Cathy; Holt, Michael; Chong, Winston
Alterations in aneurysm size and mass effect can result in alleviation or aggravation of symptoms. We assessed the effects of flow diversion with SILK stents on aneurysm sac size and associated factors. A retrospective evaluation of 14 aneurysms treated with SILK stents alone with MRI follow-up was performed. Aneurysm sac size was measured using the sequence best demonstrating the sac. Aneurysm characteristics and flow-related enhancement on time of flight images were documented. Clinical histories were reviewed for evolution of symptoms. Complete collapse of the aneurysm sac was demonstrated at three and 18 months in 2/14 aneurysms. Increase in size was observed in 2/14 aneurysms with associated persistent flow on time of flight MRA. Blister formation with aggravation of symptoms was observed in one aneurysm, and subsequent decrease in size occurred after treatment with a second SILK. The other aneurysm which increased in size initially continued to enlarge asymptomatically despite retreatment with a second SILK, however at 24 months thrombosis of the sac and decrease in size was observed. The remaining 10/14 aneurysms decreased in size. Nine had corresponding MRA occlusion and the tenth demonstrated decreased but persistent flow on the time of flight MRA. No aneurysm with MRA occlusion increased in size. Decrease in sac size was associated with MRA occlusion in our study. Persistence of flow and blistering were associated with increased sac size. As previously demonstrated flow diversion may be effective in the treatment of large aneurysms presenting with mass effect, however rates of sac obliteration in this small series were not as high as previously reported.